(Para)normalizing Rape Culture: Possession as Rape in Young Adult Paranormal Romance. Issue 1 (1st March 2021) - Herb, Annika
Abstract: Contemporary Young Adult literature is a favored genre for exploring sexual assault, yet rarely interrogates the social structures underpinning rape culture. In its representation of heterosexual relationships, Young Adult paranormal romance offers insight into the processes and structures that uphold rape culture. Genre tropes normalize abusive behavior and gender ideals, demonstrating the explicit and implicit construction of rape culture, culminating in the depiction of supernatural possession analogous to rape. Here, I reflect on power, control, rape culture, and girlhood in a textual analysis of Nina Malkin's Swoon, Becca Fitzpatrick's Hush, Hush, and Sarah Rees Brennan's The Demon's Covenant . A constructive reading reflects implicit cultural discourses presented to the girl reader, who can apply this to her own negotiation of girlhood.